How Outer Coordination Sphere Modifications Can Impact Metal Structures in Proteins: A Crystallographic Evaluation. Issue 27 (25th April 2019) - Ruckthong, Leela; Stuckey, Jeanne A.; Pecoraro, Vincent L.
Abstract: A challenging objective of de novo metalloprotein design is to control of the outer coordination spheres of an active site to fine tune metal properties. The well‐defined three stranded coiled coils, TRI and CoilSer peptides, are used to address this question. Substitution of Cys for Leu yields a thiophilic site within the core. Metals such as Hg II, Pb II, and As III result in trigonal planar or trigonal pyramidal geometries; however, spectroscopic studies have shown that Cd II forms three‐, four‐ or five‐coordinate Cd II S3 (OH2 ) x (in which x= 0–2) when the outer coordination spheres are perturbed. Unfortunately, there has been little crystallographic examination of these proteins to explain the observations. Here, the high‐resolution X‐ray structures of apo‐ and mercurated proteins are compared to explain the modifications that lead to metal coordination number and geometry variation. It reveals that Ala substitution for Leu opens a cavity above the Cys site allowing for water excess, facilitating Cd II S3 (OH2 ). Replacement of Cys by Pen restricts thiol rotation, causing a shift in the metal‐binding plane, which displaces water, forming Cd II S3 . Residue d ‐Leu, above the Cys site, reorients the side chain towards the Cys layer, diminishing the space for water accommodation yielding Cd II S3, whereas d ‐Leu below opens more space, allowing for equal Cd II S3 (OH2 ) and Cd II S3 (OH2 )2 . These studies provide insights into how to control desired metal geometries in metalloproteins by using coded and non‐coded amino acids. Abstract : Controlling coordination geometries : The high‐resolution X‐ray structures of apo‐ and mercurated proteins were compared to explain the modifications that lead to metal coordination number and geometry variation. These studies provide insights into how to control desired metal geometries in metalloproteins by using coded and noncoded amino acids.